Port's Role as a Determinant of Cruise Destination Socio-Economic Sustainability - Zagnoli, patrizia; Radicchi, Elena; Santos, M-C. (46th International Scientific Conference on Economic and Social Development, Sustainable Tourist Destinations, Varazdin, 2019)
Abstract: This article argues that the cruise terminal ports play a crucial role in the economic and socio-cultural sustainability of destinations, bridging the onshore tourism oﬀered among cruise companies, global operators, and local business and infrastructures. They support the promotion of local brands and reduce congestion. The impact of crowds on the identity of coastal cities triggeredtheattentionofacademiaandmedia,alertingfortheirnegativeimpact,speciﬁcallyfromthe Mediterranean cruises. In parallel, it raised the research interest on cruise tourism carrying capacity and ports planning the integration of cruise tourists’ ﬂow. However, previous studies focused on the residents’ and passengers’ perception of a speciﬁc destination, neglecting the port management role. This study aims to clarify the underneath dynamics that allow sustainable cruise–land visit. Employing a qualitative case study approach, it compares data obtained from secondary sources and port executives’ structured deep interviews from two leading transit ports connected with the Mediterranean. Lisbon is amongst the most popular tourism destinations and international cruise terminals; Livorno is a gateway port to Tuscany, mainly Florence and Pisa. Despite their diﬀerent patterns, inbothportsofcall,astrongconcernwithsustainabilityandareducedcongestioneﬀectare observed from the management actions on promoting the local oﬀer and on revitalizing the terminal infrastructures in order to provide comfort shopping and entertainment amenities to passengers.